Merupa Wujud Evangelikalisme di Indonesia: Suatu Usulan Awal - Yosia, Adrianus (Sekolah Tinggi Teologi SAAT, 2020)
Shaping the Form of Evangelicalism in Indonesia: A Preliminary Proposal. This article was written as a preliminary opinion to explore the